NIR-II fluorescence in lung cancer: advancing precision diagnosis and image-guided therapy - Yang, YunLong; Fu, Jiang; Xie, RangPing; Wang, Chun; Wang, Sen; Wen, Long; Yang, Yang; Liu, ChengKuan; Yi, GuiYan; Yu, Li; Zhou, HaiNing (Frontiers in Chemistry, 2026)
Lung cancer ranks among the leading causes of cancer incidence and mortality worldwide. Conventional diagnostic and therapeutic approaches remain constrained by suboptimal sensitivity, exposure to ionizing radiation, and poor overall prognosis, driving efforts to develop novel diagnostic and therapeutic strategies to improve clinical outcomes. Second near-infrared window (NIR-II) fluorescence imaging offers deep tissue penetration and high spatial resolution; accordingly, a wide array of NIR-II fluorescent probes, imaging systems, and photointerventional therapies have been developed. In this review, we summarize recent advances and applications of NIR-II in lung cancer diagnosis and treatment and discuss the design and future directions of integrated diagnostic-therapeutic (theranostic) platforms.